Relationship between WQI, heavy metal and sedimentation in Sg Kenau, Kuantan, Pahang using WQ-HeMeS Model - Nadiatul Adilah, Ahmad Abdul Ghani; Siti Aisyah, Zakaria; Putra Jaya, Ramadhansyah; Noram Irwan, Ramli; Mahyun, A. W. (IOP Science, 2021)
The purpose of this study is to investigate the relationship between water quality of river with heavy metal and sediment content in Sungai Kenau at Pahang using new developed model named WQ-HeMeS. Through this study, water quality has been analysed by using Water Quality Index (WQI) & National Water Quality Standard for Malaysia (NWQS). Water quality of river in Sungai Kenau have been observed by several test which are Dissolve Oxygen, Biochemical Oxygen Demand, Chemical Oxygen Demand, Ammoniacal Nitrogen, Total Suspended Solid, Phosphorus and Nitrogen as Nitrate. Meanwhile, the sedimentation rate was determine using Schoklistch method and Duboy method. There are 2 condition for heavy metal considered in the analysis which are heavy metal in water and heavy metal in sediment. Heavy metal in water was tested using laboratory tools named as Atomic Absorption Spectroscopy (AAS) while heavy metal in sediment have been determined by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The classification of heavy metal in water have been done based on NWQS meanwhile heavy metal in sediment were observed based on Index of Geo-Accumulation and Metal Contamination Factor. After collecting all result from lab testing, the the relationship of water quality, sedimentation rate and heavy metal rate both in water and sediment was determine using generated model. Based on Malaysia WQI Standard, the result shown that water in Sungai Kenau is classified as Class I which means as for water supply, there are no treatment is necessary.